Student's Perception of Improving Speaking Skills Through Video Recording Task - Tukan, Fransiska M. Ena (CV. Rustam, 2024)
Speaking is one of the most important skills to enhance effective communication. The research aimed to find out (1) students' perception of improving speaking skills through video recording tasks and (2) student's feelings when doing video recording tasks. The research was qualitative. The participants were ten students taking part in the Speaking 1 class in the academic year 2023/2024 at the English Department Program. Data was collected through observation, interviews, and a questionnaire listed. Findings showed student's responses to the speaking task, such as (1) students enjoyed making video recordings, (2) students often watched the video many times before being handed over to the lecturer, (3) students often reviewed and exercised through their video clips, (4) students often evaluated their video to recognize their speaking mistakes, (5) students always practiced their speaking before recording their video. In addition, relating to the students' feelings, data showed that students were happy to do a video recording task. They were confident in using the English language. They mentioned that it was easy to use the application for practicing. They could learn how to use the applications for editing a video. Therefore, these class activities were useful for helping students with their speaking. Their process can be seen in the progress which is going on.